Psychological Disclosure of a World within Human Mind: A Study of Eugene O’neill’s The Emperor Jones (Journal of Imam Al-Kadhim College, 2023)
The Emperor Jones is a psychological study of the mind, fears, visions, and dreams of Brutus Jones, the protagonist of the work. In the same piece, Tom-Tom symbolizes the last heartbeat and death of a person. Jones's awareness is expressed in his technique of cinematic flashbacks linking past and present. Symbolism and psychology merge here and the whole play becomes one long drama. Eugene O'Neill compresses the summary of an event of trauma into eight scenes, expressing the personal and collective trauma of an individual and a society caused by a distorted sense of self and one’s concept of identity with respect to political repression as well as cultural colonization. By externalizing the symptoms of psychological trauma in the reconstruction of Black identity together with nationalism, O'Neill’s play symbolically lets readers participate in perceptions of the evolution of trauma and the ongoing threat of psychosocial trauma.
Keywords: Keywords: Trauma, Black Nationalism, identity, expressionist drama